PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MOBILE LEARNING ADVENTURE MAZE CHASE PADA PEMBELAJARAN IPAS DI KELAS IV SD - Rosi Amelia; Treny Hera; Kiki Aryaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Based on initial observations at SD Negeri 98 Palembang conducted by researchers, problems were found, namely Researchers obtained information that the science learning process uses teaching materials in the form of modules, printed books and pictures and uses lecture learning methods so that students experience boredom in learning activities. Therefore, the solution to this problem is that researchers want to develop learning media based on mobile learning adventure maze chase in science learning with the ADDIE model. This research method uses the research and development method with the limits of expert assessment and practicality research. Expert assessments are carried out on material experts and media experts, while practicality is with teachers and students. Data collection techniques use observation, questionnaires and documentation, while data analysis techniques use average scores. The results of the development stage are to produce learning media products based on mobile learning adventure maze chase in science learning in grade IV of elementary school. The results of the media expert assessment show that the learning media based on mobile learning adventure maze chase with an average score of 41.5. Thus, it can be concluded that learning media based on mobile learning adventure maze chase in science learning in grade IV of elementary school is included in the valid category. From the results of practitioners, namely teachers and students, an average score of 45.05 was obtained, it can be concluded that the practicality of learning media based on mobile learning adventure maze chase in science learningin grade IV of elementary school is included in the very feasible category